THE SUBMICROSCOPIC ORGANIZATION OF AXON MATERIAL ISOLATED FROM MYELIN NERVE FIBERS - De Robertis, E. (The Rockefeller University Press, 1953)
A technique has been developed for the extrusion of axon material from myelinated nerve fibers. This material is then compressed and prepared for observation with the electron microscope. All the stages of preparation and purification of the axon material can be checked microscopically and in the present paper they are illustrated with phase contrast photomicrographs. Observation with the electron microscope of the compressed axons showed the presence of the following components: granules, fibrils, and a membranous material. Only the larger granules could be seen with the ordinary microscope. A considerable number of dense granules were observed. Of these the largest resemble typical mitochondria of 250 mµ by 900 mµ. In addition rows or small clusters of dense granules ranging in diameter from 250 to 90 mµ were present. In several specimens fragments of a membrane 120 to 140 A thick and intimately connected with the axon were found. The entire axon appeared to be constituted of a large bundle of parallel tightly packed fibrils among which the granules are interspersed. The fibrils are of indefinite length and generally smooth. They are rather labile structures, less resistant in the rat than in the toad nerve. They varied between 100 and 400 A in diameter and in some cases disintegrated into very fine filaments (less than 100 A thick). The significance is discussed of the submicroscopic structures revealed by electron microscopy of the material prepared in the way described.